Activity Based Costing (ABC) Implementation In Determining Rates for Inpathement Services At Dr. Tadjuddin chalid makassar - Musfira; Azis, Muhammad; S, Masnawaty (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
This research aimed: (1) To find out the Determination of Rates for Inpatient Services at RSUP Dr. Tadjuddin Chalid Makassar, and (2) To find out the Analysis of the Application of Activity Based Costing (ABC) in Determining Inpatient Service Rates at Dr. Tadjuddin Chalid Makassar. The variables of this research are Activity Based Costinng (ABC). The population of this research are all activities in the inpatient room at RSUP Dr. Tajuddin Chalid Makassar, and the sample are inpatient rooms in the VIP room, class I, class II, and class III at RSUP Dr. Tadjuddin Chalid Makassar during 2022. The data were collected by interview and documentation. The data obtained were analyzed using descriptive qualitative. The results of this research suggest that the calculation of inpatient rates uses Activity Based Costing (ABC), when compared to the rates used by Dr. Tadjuddin Chalid Makassar gave bigger results for VIP class and class III, while for class I and class II it gave smaller results. The difference in rates that occur is due to the imposition of overhead costs on each product. Activity Based Costing (ABC) has been able to allocate activity costs to each room appropriately based on the consumption of each activity.